The Supervisory treatment of market risks : consultative proposal - Basel Committee on Banking Supervision; Bank for International Settlements (Basle Bank for International Settlements, 1993)
The Basel Committee on Banking Supervision ("the Committee") is issuing the attached proposals for the supervisory treatment of market risks incurred by banks. Market risk is the risk of losses in on and offbalance- sheet positions arising from movements in market prices, including interest rates, exchange rates and equity values. The basic thrust of the proposals is to require capital requirements for open positions in debt securities, equities and foreign exchange. It is intended that, following a comment period, the proposed new capital requirements would be integrated with the Basle Capital Accord ("the Accord' )
Keywords: Banks and Banking; BANKS; CAPITAL; MANAGEMENT; RISK MANAGEMENT; BANK RESERVES